2023
DOI: 10.3390/foods12091753
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of Functional Microorganisms in Representative Traditional Fermented Dongcai from Different Regions of China

Abstract: Dongcai is loved for its delicious flavor and nutritional value. The microorganisms in Dongcai play a vital role in their flavor, quality, and safety, and the microbial communities of Dongcai vary greatly from region to region. However, it remains unknown what the predominant microorganisms are in different traditional Dongcai and how they affect its flavor. The objective of this study is to explore the microbial diversity of traditional fermented Dongcai in three representative Chinese regions (Tianjin, Sichu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Burkholderia‐Caballeronia‐Paraburkholderia accounts for about 0.1% of bacteria in the 0–5 days and during the mid‐fermentation stage, its proportion increases to 0.5%, accounting for 0.37% in the finished BLMJ. Burkholderia‐Caballeronia‐Paraburkholderia are dominant bacteria in a variety of fermented foods, such as fermented Dongcai, Sufu, Doubanjiang (Yang et al ., 2021; Wu et al ., 2022; Jiang et al ., 2023). A previous study has shown that Burkholderia–Caballeronia–Paraburkholderia play an important role in the flavour formation of fermented Sufu at the early fermentation stage (Wu et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Burkholderia‐Caballeronia‐Paraburkholderia accounts for about 0.1% of bacteria in the 0–5 days and during the mid‐fermentation stage, its proportion increases to 0.5%, accounting for 0.37% in the finished BLMJ. Burkholderia‐Caballeronia‐Paraburkholderia are dominant bacteria in a variety of fermented foods, such as fermented Dongcai, Sufu, Doubanjiang (Yang et al ., 2021; Wu et al ., 2022; Jiang et al ., 2023). A previous study has shown that Burkholderia–Caballeronia–Paraburkholderia play an important role in the flavour formation of fermented Sufu at the early fermentation stage (Wu et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The decrease of 2‐octanone in the early and middle stages of fermentation may be related to the growth and reproduction of Staphylococcus . A previous study found that Staphylococcus is one of the main microorganisms that dominate salt, acid, amino nitrogen and carbohydrate metabolism during the fermentation process of Dongcai (Jiang et al ., 2023).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation